Pengaruh Literasi Keuangan, Perilaku Keuangan dan Toleransi Risiko Terhadap Keputusan Investasi Mahasiswa (Pada Univervitas Semarang) - Novanda Zoelva Mina Raya; Johanis Souisa; Sasi Fadillah; Dhiyas Vonny Wulan Febriana (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Planning an investment in personal financial management especially for students is crucial because investment is a process of learning to manage finances, starting now and in the future. Low knowledge about investment decisions often makes students experience fraud, because offers from investment returns are also very tempting. Based on the phenomenon, this study aims to determine the effect of financial literacy, financial behavior, and risk tolerance on investment decisions. This research was conducted by distributing questionnaires to respondents with the criteria of students at the University of Semarang majoring in S1 Management class of 2020 and interested in or have already invested in the capital market. The number of research respondents was 96 students and data management used SPSS 23 with multiple regression analysis techniques. The results of this study state that financial literacy has a positive and insignificant effect on investment decisions, while financial behavior and risk tolerance have a positive and significant effect on investment decisions of Semarang University students majoring in Management S1 class of 2020.